Visual evoked Potential (VEP): Physiological variation in normal children and adolescent up to 20 years of age - Wadhera, Jyoti; Dudhmal, Vandana (International Journal of Medical Research and Review, 2015)
Introduction: Visual evoked Potential is the electrical potential difference recorded from the surface of scalp in response to Visual stimuli. It represents a resultant response of cortical as well as subcortical areas to photostimulation. Although various studies have been done on visual evoked potential but there are few studies from India only. Therefore this study was planned to study visual evoked potentials by recording battery of N70, P100 & N155 waveform in different age groups of normal healthy children. Methods: Present study was conducted in department of Physiology of Tertiary care teaching hospital. 50 healthy patients were included in two groups, below 5 years and 6- 20 years. Visual evoked Potential has been recorded and their physiological Variation has been observed. Results: It was seen that mean value and standard deviation of amplitude of N70 wave in left eye showed significant decrease in age group of 4 to 5 years. Mean value and standard deviation of amplitude of P 100 wave in right eye showed significant decrease in age group of 4 to 5 years. Other values were not significant. Conclusion: Age and sex have little impact on Visual evoked Potential in children. Eye dominance has been observed more commonly.